Artificial Intelligence for Wireless Communication Systems Technology and Applications - Sur, Samarendra Nath (Taylor & Francis Group, 2025)
The text provides a comprehensive study of the application of advanced artificial intelligence in next-generation wireless communications with a focus on theory, standardization, and core development. It further highlights artificial intelligence-enabled intelligent architecture for 6G networks.
Description based on publisher supplied metadata and other sources
Keywords: Funknetz; Künstliche Intelligenz; Wireless communication systems